Clinical review of the clinical necessity of lumbar punctures performed on adults at National District Hospital Emergency Department - Suné Geldenhuys; Cecil Boltman; Wilhelm J. Steinberg; Johan Botes; Cornel van Rooyen (South African Family Practice)
Background: Previous studies have found that indications for lumbar punctures (LPs) are managed differently, which raises the question of whether all LPs performed are clinically necessary. This study aimed to determine whether unnecessary (clinically not indicated) LPs were being performed at a district hospital in the Free State, South Africa.